Exploring GPS Observations of Postseismic Deformation Following the 2012 MW7.8 Haida Gwaii and 2013 MW7.5 Craig, Alaska Earthquakes: Implications for Viscoelastic Earth Structure. Issue 7 (5th July 2021) - Guns, K. A.; Pollitz, F. F.; Lay, T.; Yue, H.
Abstract: The Queen Charlotte‐Fairweather Fault (QC‐FF) system off the coast of British Columbia and southeast Alaska is a highly active dextral strike‐slip plate boundary that accommodates ∼50 mm/yr of relative motion between the Pacific and North America plates. Nine M W  ≥ 6.7 earthquakes have occurred along the QC‐FF system since 1910, including a M S (G‐R) 8.1 event in 1949. Two recent earthquakes, the October 28, 2012 Haida Gwaii ( M W 7.8) and January 5, 2013 Craig, Alaska ( M W 7.5) events, produced postseismic transient deformation that was recorded in the motions of 25 nearby continuous Global Positioning System (cGPS) stations. Here, we use 5+ yr of cGPS measurements to characterize the underlying mechanisms of postseismic deformation and to constrain the viscosity structure of the upper mantle surrounding the QC‐FF. We construct forward models of viscoelastic deformation driven by coseismic stress changes from these two earthquakes and explore a large set of laterally heterogeneous viscosity structures that incorporate a relatively weak back‐arc domain; we then evaluate each model based on its fit to the postseismic signals in our cGPS data. In determining best‐fit model structures, we additionally incorporate the effects of afterslip following the 2012 event. Our results indicate the occurrence of a combination of temporally decaying afterslip and vigorous viscoelastic relaxation of the mantle asthenosphere. In addition, our best‐fit viscosity structure (transient viscosity of 1.4–2.0 × 10 18  Pa s; steady‐state viscosity of 10 19  Pa s) is consistent with the range of upper mantle viscosities determined in previous studies of glacial isostatic rebound and postseismic deformation. Plain Language Summary: Off the coasts of British Columbia and southeastern Alaska, lies a tectonic plate boundary called the Queen Charlotte‐Fairweather Fault system. This system is accommodating rapid shearing motion between the Pacific and North America plates and has a recorded history of large‐magnitude earthquakes. Two such earthquakes occurred along this boundary within 3 months of each other in late 2012 and early 2013. These earthquakes provide an opportunity to explore subsurface Earth structure, as the surface motions they induced, both during and after the earthquakes, were measured by continuously observing Global Positioning System (GPS) stations onshore. These instruments measure how much the surface of the Earth moved in any direction, and we use over 5 years of these measurements to investigate how the upper mantle of the Earth responded to the stresses caused by the two earthquakes. We use this information to constrain viscosity values for the upper mantle in this region. In our investigations, we find that in addition to measuring a strong upper mantle response to the earthquakes, GPS observations are also likely measuring fault slip that occurred after the 2012 earthquake, along both a dipping fault plane underneath the Haida Gwaii islands and a vertical fault plane offshore. Key Points: The postseismic transient deformation caused by the 2012 and 2013 events is characterized by both afterslip and viscoelastic relaxation 5+ years of cGPS data constrain a biviscous viscosity structure in the upper mantle asthenosphere under a sliver of Western North America Additional postseismic campaign GPS data suggest afterslip occurred on both a dipping and a vertical fault plane following the 2012 event